Mortality by causes in HIV-infected adults: comparison with the general population - Floristan Yugo; Irisarri Fátima; Egüés Nerea; Moreno-Iribas Conchi; Aldaz Pablo; Sola-Boneta Julio; Martínez-Artola Víctor; Sagredo Mirian; Castilla Jesús (BMC, 2011)
Abstract Background We compared mortality by cause of death in HIV-infected adults in the era of combined antiretroviral therapy with mortality in the general population in the same age and sex groups. Methods Mortality by cause of death was analyzed for the period 1999-2006 in the cohort of persons aged 20-59 years diagnosed with HIV infection and residing in Navarre (Spain). This was compared with mortality from the same causes in the general population of the same age and sex using standardized mortality ratios (SMR). Results There were 210 deaths among 1145 persons diagnosed with HIV (29.5 per 1000 person-years). About 50% of these deaths were from AIDS. Persons diagnosed with HIV infection had exceeded all-cause mortality (SMR 14.0, 95% CI 12.2 to 16.1) and non-AIDS mortality (SMR 6.9, 5.7 to 8.5). The analysis showed excess mortality from hepatic disease (SMR 69.0, 48.1 to 78.6), drug overdose or addiction (SMR 46.0, 29.2 to 69.0), suicide (SMR 9.6, 3.8 to 19.7), cancer (SMR 3.2, 1.8 to 5.1) and cardiovascular disease (SMR 3.1, 1.3 to 6.1). Mortality in HIV-infected intravenous drug users did not change significantly between the periods 1999-2002 and 2003-2006, but it declined by 56% in non-injecting drug users (P = 0.007). Conclusions Persons with HIV infection continue to have considerable excess mortality despite the availability of effective antiretroviral treatments. However, excess mortality in the HIV patients has declined since these treatments were introduced, especially in persons without a history of intravenous drug use.